2017
DOI: 10.1080/00918369.2017.1391017
|View full text |Cite
|
Sign up to set email alerts
|

Scrutinizing Homophobia: A Model of Perception of Homosexuals in Russia

Abstract: We aimed to develop and validate a model of associations of perceived threat of homosexuals with lay beliefs about causes of homosexuality, group entitativity of homosexuals, approval of social action strategies targeting homosexuals, and support for their rights using original Russian-language measures. We tested the model in two samples of social network users (n = 1,007) and student respondents (n = 292) using structural equation modeling and path analysis. Attribution of homosexuality to social causes was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 69 publications
0
25
0
2
Order By: Relevance
“…Therefore, only few psychologists deal with LGBTQ issues in research, counselling, and education. These active and visible people include Dmitri Isaev (Isaev, 2016), Evgeni Osin (Gulevich, Osin, Isaenko, & Brainis, 2018), Maria Sabunaeva and Hana Korchemnaya. Usually, there is no request from the government for any expertise in LGBTQ issues.…”
Section: A) Russiamentioning
confidence: 99%
“…Therefore, only few psychologists deal with LGBTQ issues in research, counselling, and education. These active and visible people include Dmitri Isaev (Isaev, 2016), Evgeni Osin (Gulevich, Osin, Isaenko, & Brainis, 2018), Maria Sabunaeva and Hana Korchemnaya. Usually, there is no request from the government for any expertise in LGBTQ issues.…”
Section: A) Russiamentioning
confidence: 99%
“…ПРОДОЛЖАЯ И. С. КОНА 2014; Шорыгин, 2017] и на многие другие темы. Поскольку наследие И. С. Кона далеко выходит за пределы собственно социологических исследований, на него опираются и многие психологи, занимающиеся проблемами гендерных норм и социализации, гендерной идентичности и другими аспектами развития личности [Александрова, Баркова, 2015;Исаев, 2016;Клецина, Иоффе, 2017;Иоффе, 2018;Gulevich et al 2018]. Можно сказать, что его влияние на российские социальные науки устойчиво и многопланово.…”
Section: вместо заключенияunclassified
“…Campaigns for public awareness for Lesbian, Gay, Bisexual, and Transgender (LGBT) rights have emerged in many places. Despite increasing LGBT visibility globally, there are still many places in the world where the legal status of homosexuals is inferior to that of the heterosexual majority (Gulevich, Osin, Isaenko, & Brainis, 2018). A multi-country survey conducted by the Pew Research Center (2013) showed that there is an equally widespread rejection for homosexuality in predominantly Muslim nations and in Africa as well as in parts of Asia and in Russia despite of broad acceptance of homosexuality in North America, the European Union, and Latin America.…”
Section: Introductionmentioning
confidence: 99%
“…), and behavioral (discrimination, lying, cheating, harassment, etc. ) outcomes (Gulevich et al, 2018;Riek, Mania, & Gaertner, 2006;Stephan et al, 2016). Responses to intergroup threat are determined by whether the perceived threats are symbolic or realistic.…”
Section: Introductionmentioning
confidence: 99%